The smallest angiosperm genomes may be the price for effective traps of bladderworts - Zedek, František; Šmerda, Jakub; Halasová, Aneta; Adamec, Lubomír; Veleba, Adam; Plačková, Klára; Bureš, Petr (Annals of botany, 2024)
BACKGROUND: Species of the carnivorous family Lentibulariaceae exhibit the smallest genomes in flowering plants. We explored the hypothesis that their minute genomes result from the unique mitochondrial cytochrome c oxidase (COX) mutation. The mutation may boost mitochondrial efficiency, which is especially useful for suction-bladder traps of Utricularia, but also increase DNA-damaging reactive oxygen species, leading to genome shrinkage through deletion-biased DNA repair. We aimed to explore the impact of this mutation on genome size, providing insights into genetic mutation roles in plant genome evolution under environmental pressures. METHODS: We compiled and measured genome and mean chromosome sizes for 127 and 67 species, respectively, representing all three genera (Genlisea, Pinguicula and Utricularia) of Lentibulariaceae. We also isolated and analysed COX sequences to detect the mutation. Through phylogenetic regressions and Ornstein-Uhlenbeck models of trait evolution, we assessed the impact of the COX mutation on the genome and chromosome sizes across the family. RESULTS: Our findings reveal significant correlations between the COX mutation and smaller genome and chromosome sizes. Specifically, species carrying the ancestral COX sequence exhibited larger genomes and chromosomes than those with the novel mutation. This evidence supports the notion that the COX mutation contributes to genome downsizing, with statistical analyses confirming a directional evolution towards smaller genomes in species harbouring these mutations. CONCLUSIONS: Our study confirms that the COX mutation in Lentibulariaceae is associated with genome downsizing, probably driven by increased reactive oxygen species production and subsequent DNA damage requiring deletion-biased repair mechanisms. While boosting mitochondrial energy output, this genetic mutation compromises genome integrity and may potentially affect recombination rates, illustrating a complex trade-off between evolutionary advantages and disadvantages. Our results highlight the intricate processes by which genetic mutations and environmental pressures shape genome size evolution in carnivorous plants.
Keywords: molekulární evoluce; Genome Size; recombination rate; genome size; Phylogeny; Magnoliopsida; Evolution, Molecular; Carnivory; mutace; Pinguicula; Genome, Plant; smallest genomes; respirační komplex IV; délka genomu; fylogeneze; cytochrome oxidase; Utricularia; Electron Transport Complex IV; Lentibulariaceae; Mutation; genom rostlinný; Genlisea; chromosome size